Effects of a CO2 Border Adjustment on Downstream Industries - André Wolf (Wirtschaftsdienst)
Abstract This article analyses the cost implications of an EU Carbon Border Adjustment Mechanism (CBAM) for downstream industries in Germany. The restriction to a few basic industries as envisaged in the EU Commission’s proposal is expected to lead to only a slight increase in input costs for downstream manufacturers. This also holds if the CO2 intensities occurring in the countries of origin are used to determine the level of the border adjustment. One reason for this, apart from the restriction to a few basic materials and to direct emissions, is the small share of imports from third countries. To strengthen the steering effect of a CBAM, the inclusion of emissions at upstream production levels therefore seems manageable, to the extent that they apply to intermediate inputs that are also subject to the EU-ETS. In the long term, a CBAM should not be thought of as an end in itself, but as one of several steps towards an international climate club.